2023
DOI: 10.1021/acs.organomet.3c00234
|View full text |Cite
|
Sign up to set email alerts
|

Heterolytic versus Homolytic: Theoretical Insight into the Ni0-Catalyzed Ph–F Bond Activation

Jian-Sen Wang,
Xiao-Xia You,
Rong-Lin Zhong
et al.

Abstract: The Ni0-catalyzed borylation of fluorobenzene (PhF) was theoretically investigated. Density functional theory (DFT) calculations disclosed that the Ph–F bond activation occurred heterolytically via an unprecedented nucleophilic aromatic substitution reaction (SNAr) assisted by an sp2–sp3 diboron complex [B2nep2·(OPh)]‑Na+, which forms a Ni0-ate complex as an active species. The diboron-ate complex stabilizes the transition state of the Ph–F bond activation through three interactions, a Ni···O coordination, a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Interestingly, despite C being somewhat more stable (2.7 kcal mol −1 ) than E , the Ni 0 (silyl)-ate complex is considered a plausible active species, because the pre-catalyst Ni 0 (cod) 2 is inactive for the inert C(sp 2 )–F bond activation. 20,36 As shown in Scheme S1,† in intermediate E , two cod molecules coordinate to the Ni 0 -center in an η 2 manner, which is more stable than a single cod molecule coordinated in an η 4 manner.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, despite C being somewhat more stable (2.7 kcal mol −1 ) than E , the Ni 0 (silyl)-ate complex is considered a plausible active species, because the pre-catalyst Ni 0 (cod) 2 is inactive for the inert C(sp 2 )–F bond activation. 20,36 As shown in Scheme S1,† in intermediate E , two cod molecules coordinate to the Ni 0 -center in an η 2 manner, which is more stable than a single cod molecule coordinated in an η 4 manner.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of Ni 0 (cod) 2 , the coordination of the silyl anion to the Ni 0 -center could not be ruled out because the coordination energy between Ni and the silyl anion is −52.5 kcal mol −1 , forming a Ni 0 (silyl)-ate complex, K + [Ni 0 (cod) 2 (SiEt 3 )] − , E. Interestingly, despite C being somewhat more stable (2.7 kcal mol −1 ) than E, the Ni 0 (silyl)-ate complex is considered a plausible active species, because the pre-catalyst Ni 0 (cod) 2 is inactive for the inert C(sp 2 )-F bond activation. 20,36 As shown in Scheme S1, † in intermediate E, two cod molecules coordinate to the Ni 0center in an η 2 manner, which is more stable than a single cod molecule coordinated in an η 4 manner.…”
Section: Reaction Mechanism Of C(sp 3 )-F Bond Activation With Et 3 S...mentioning
confidence: 99%
See 2 more Smart Citations
“…While the C–F activation of polyfluorinated arenes is well established for many transition-metal and low-valent main-group complexes, the selective C–F functionalization of monofluorinated arenes is challenging due to the high bond dissociation energy (BDE) of the C(sp 2 )–F bond (125.6 kcal mol –1 for Ph–F vs 114 kcal mol –1 for C 6 F 6 and 65.1 kcal mol –1 for Ph–I) . The C–F activation of monofluorinated arenes provides opportunities for orthogonal cross-coupling strategies or the late-stage functionalization of substituted arenes, , and numerous stoichiometric, catalytic, and mechanistic studies have been reported to date using nickel complexes. …”
Section: Introductionmentioning
confidence: 99%